Transcranial Direct Current Stimulation Over Motor Areas Improves Reaction Time in Parkinson's Disease - Sadler, Christin M.; Kami, Aline Tiemi; Nantel, Julie; Lommen, Jonathan; Carlsen, Anthony N. (Frontiers in Neurology, 2022)
Background: Transcranial direct current stimulation (tDCS) has been shown to modulate cortical motor excitability and improve bradykinesia symptoms in Parkinson’s Disease. It is unclear how targeting different cortical motor areas with tDCS may differentially influence upper limb function for individuals diagnosed with PD. Objective: This study investigated whether anodal tDCS applied separately to primary motor cortex and supplementary motor area would improve upper limb function for individuals with Parkinson’s Disease. In addition, a startling acoustic stimulus was used to differentiate between the effect of stimulation on motor preparatory and initiation processes associated with upper limb movements. Methods: Eleven participants with idiopathic Parkinson’s Disease performed two upper limb simple reaction time tasks involving elbow extension or a button press before and after either anodal tDCS or sham tDCS was applied over primary motor cortex or supplementary motor area. A loud, startling stimulus was presented on a selection of trials to involuntarily trigger the prepared action. Results: Anodal tDCS led to improved premotor reaction time in both tasks, but this was moderated by reaction time in pre-tDCS testing, such that individuals with slower pre-tDCS reaction time showed the greatest reaction time improvements. Startle-trial reaction time was not modified following tDCS, suggesting that the stimulation primarily modulated response initiation processes. Conclusion: Anodal tDCS improved response initiation speed, but only in slower reacting individuals with PD. However, no differences attributable to tDCS were observed in clinical measures of bradykinesia or kinematic variables, suggesting that reaction time may represent a more sensitive measure of some components of bradykinesia.